2015
DOI: 10.13075/ijomeh.1896.00343
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A – Application, sources of exposure and potential risks in infants, children and pregnant women

Abstract: Bisphenol A (BPA) is used in the chemical industry as a monomer in the production of plastics. It belongs to a group of compounds that disturb some of the functions of human body, the endocrine system in particular. Extensive use of BPA in manufacturing products that come in contact with food increases the risk of exposure to this compound, mainly through the digestive tract. Literature data indicate that exposure to bisphenol A even at low doses may result in adverse health effects. The greatest exposure to B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 110 publications
2
74
0
2
Order By: Relevance
“…Studies have shown that the developing immune system is highly sensitive to BPA exposure. In humans, prenatal and postnatal environmental BPA exposure is associated with various autoimmune diseases and inflammation during childhood and adulthood, including allergy, asthma and obesity (Spanier et al, 2012;Trasande et al, 2012;Mikołajewska et al, 2015). In animals, early-life exposure to BPA may produce considerable adverse effects to the immune system, such as cytokine secretion changes, immune-associated gene expression, T helper (Th)1/Th2 cell shifts, decrease in regulatory T cell (Treg) number, immune response abnormality, and allergic inflammation in offspring mice during the life course (Yoshino et al, 2004;Yan et al, 2008;Midoro-Horiuti et al, 2010;Bauer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the developing immune system is highly sensitive to BPA exposure. In humans, prenatal and postnatal environmental BPA exposure is associated with various autoimmune diseases and inflammation during childhood and adulthood, including allergy, asthma and obesity (Spanier et al, 2012;Trasande et al, 2012;Mikołajewska et al, 2015). In animals, early-life exposure to BPA may produce considerable adverse effects to the immune system, such as cytokine secretion changes, immune-associated gene expression, T helper (Th)1/Th2 cell shifts, decrease in regulatory T cell (Treg) number, immune response abnormality, and allergic inflammation in offspring mice during the life course (Yoshino et al, 2004;Yan et al, 2008;Midoro-Horiuti et al, 2010;Bauer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Bisphenol A is an estrogenic compound and is coming to the body from plastics (14) and thermal print paper (15). Several clinical studies show that humans exposed to bisphenol A are more likely to incur reproductive disorders like reduction of spermatogenesis, decreased testosterone production or malformation of the genitals or induction of tumors like mammary carcinoma, immune function and allergy, obesity and diabetes (4,16). Bisphenol A, a common and widely utilized chemical contaminant acting as endocrine disruptor, accumulates in adipose tissue and may affect adipocyte metabolic and inflammatory functions.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical nomenclature of Bisphenol C is 2,2-Bis(4-hidroxy-3-methylphenyl) 24 These data suggest that both children and adults may be exposed to BPA higher than t-TDI mainly by dietary exposure and might be affected by toxic health outcomes. Although a t-TDI was not found for bisphenol analogs, Wu et al 25 reported that bisphenol analogs in foodstuffs are found as bps <0.01 ng/g bpa 0.125 ng/g bpf <0.05 ng/g bpp <0.025 ng/g bpaf <0.01 ng/g In U.S. between 2008-2012 which seem to be lower than BPA.…”
mentioning
confidence: 91%